Estudio de prefactibilidad para la instalación de una planta productora de pavo ahumado deshilachado envasado al vacío - Ferreyros Torres, Fernando Carlos (2021)
The research project contained in this document is focused on determining the feasibility of the installation of a vacuum-packed shredded smoked turkey production plant in Peru. In regards of the product, it will be displayed to the final consumer in 250 gram bags carrying a label with the product’s information; however, its distribution towards the retailer will be in boxes containing 50 bags each. The market considered for this project is located in metropolitan Lima and has been segmented based on the final consumers ages, between 15 and 44, and their districts of residence, those being zones 6, 7 and 8. As a result of this market segmentation, the project’s demand was calculated from 2020 until 2024; and its peak will be reached during the final year, 98,947 boxes of finished product. As to location planning, the most convenient location for the facilities was discovered to be the district of Lurin in Lima. The Factor Rating Method and the Brown & Gibson Method were applied for this assessment. In order to determine the production limit, the following criteria was considered: market, technology, productive resources and break-even point. The results showed that the market would be the one to limit the production: 98,947 boxes of finished product. In addition, the manufacturing process, equipment selection and plant layout were carefully revised in order to meet the projects expectations. Finally, the investment needed for the project’s implementation and the opportunity cost were estimated to be S/4,687,56 and 16.58%, respectively. The conclusion of the financial assessment was that the project is profitable because the NPV equals S/10,412,607.99 and the IRR equals 186.41%.